2019
DOI: 10.32725/jab.2019.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification and applications of neuroactive silk proteins: a narrative review

Abstract: In traditional medicine, natural silk is regarded as a cognitive enhancer and a cure for ameliorating the symptoms of heart disease, atherosclerosis, and metabolic disorders. In this review, general characteristics of both silk proteins, fibroin and sericin, extracted from silkworm Bombyx mori and their potential use in the neuronal disorders was discussed. Evidence shows that silk proteins exhibit neuroprotective effects in models of neurotoxicity. The antioxidant, neuroprotective, and acetylcholinesterase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…It was reported that BF-7 treatment after MCAO significantly decreased infarct volume in the rat brain [ 21 ]. To the best of our knowledge, neuroprotective effects in other cocoon hydrolysate were not investigated, but only in BF-7 [ 38 ]. In this study, we firstly demonstrated the neuroprotective effect of BF-7 against transient forebrain ischemia in gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BF-7 treatment after MCAO significantly decreased infarct volume in the rat brain [ 21 ]. To the best of our knowledge, neuroprotective effects in other cocoon hydrolysate were not investigated, but only in BF-7 [ 38 ]. In this study, we firstly demonstrated the neuroprotective effect of BF-7 against transient forebrain ischemia in gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been found that PD is followed by the production of tyrosinases that are involved in neurodegeneration [ 136 ]. In PD, overexpression of tyrosinases causes hydroxylation, which results in a reduction in dopamine content and the production of ROS, which both cause neuronal cell death [ 136 , 137 ].…”
Section: Silk Fibroin In the Context Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…SS has been found as an inhibitor of tyrosinases [ 138 ], while the peptides of SF have shown neuroprotection against 6-OHDA-induced neurodegeneration [ 137 ]. SF-derived peptides preserved the viability of dopaminergic neurons in response to 6-hydroxydopamine neurotoxicity in a PD animal model induced by 6-OHDA [ 130 ].…”
Section: Silk Fibroin In the Context Of Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…SP is a bioactive material that is extracted from the silkworm Bombyx mori and has a potential value in traditional medicine and as a dietary supplement for a broad range of health-related purposes [47]. Recent research has shown that SP has anti-diabetic, anti-tumor, anti-oxidant, anti-bacterial, cell proliferation, and wound healing effects [31,[48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%